PENGARUH LEVERAGE DAN KUALITAS AUDIT TERHADAP COST OF CAPITAL DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL PADA PERUSAHAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - MUHAMMAD JALIL; SITI AISYAH BAHAR (Fakultas Ekonomi Universitas Islam Indragiri, 2022)
This study aims to obtain empirical evidence and analyze the effect of leverage, and audit quality on the cost of capital with firm size as a control variable. The research population is mining companies listed on the Indonesia Stock Exchange in 2018-2020. The selection of research samples using purposive sampling technique, so that obtained as many as 30 companies or 90 samples that was used in the study. The analysis technique in this research is multiple linear regression method, classical assumption, and descriptive statistical test. The results showed that leverage had no effect on the cost of capital, while audit quality had an effect on the cost of capital and firm size as a control variable had an effect on the cost of capital. Adjusted R Square value of 0.130 or 13% which indicates that 13% of the dependent variable can be explained by independent variables and control variables while the remaining 87% is influenced by other factors.